2020
DOI: 10.1002/2050-7038.12567
|View full text |Cite
|
Sign up to set email alerts
|

Techno‐economic evaluation of renewable energy systems combining PV‐WT‐HKT sources: Effects of energy management under Ecuadorian conditions

Abstract: Sustainable development reached a new energy paradigm in recent decades, by promoting renewable generation technologies. The present study performs a techno-economic analysis of several hybrid energy systems that combine wind generators, photovoltaic systems, hydrokinetic turbines, lead acid batteries, and diesel generators in southern Ecuador. From real data, the sizing optimization of each renewable system was done under three proposed energy control algorithms. Then, the combinations of renewable systems ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…Due to the high altitude, the location experiences a high sky clearness index (CI) and, thus, high solar radiation. Te mathematical expression used to calculate the PV power output in HOMER Pro software is presented using equations ( 1) and ( 2) [37][38][39].…”
Section: Solar Photovoltaicmentioning
confidence: 99%
“…Due to the high altitude, the location experiences a high sky clearness index (CI) and, thus, high solar radiation. Te mathematical expression used to calculate the PV power output in HOMER Pro software is presented using equations ( 1) and ( 2) [37][38][39].…”
Section: Solar Photovoltaicmentioning
confidence: 99%
“…In another study, P. Arevalo et al [20] presented an interesting technical-economic analysis of different combined hybrid energy systems, such as wind generators, photovoltaic systems, hydrokinetic turbines, batteries and diesel generators in southern Ecuador.…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing the available literature, it has been found that despite the existence of multiple studies about the implementation of renewable resources in hybrid systems worldwide [13][14][15][16][17], very few are located in Ecuador [18]- [20], and almost none includes a sensitivity analysis. Being a developing country, with remote communities with poor electrification, but a high energy potential in their natural resources, it is necessary to carry out as many studies as possible, considering local characteristics.…”
Section: Introductionmentioning
confidence: 99%